Dark pulse emission in nonlinear polarization rotation-based multiwavelength mode-locked erbium-doped fiber laser - Tiu, Z.C.; Tan, S.J.; Ahmad, Harith; Harun, Sulaiman Wadi (Optical Society of America, 2014)
We experimentally show dark pulse generation in all-normal dispersion multiwavelength erbium-doped fiber laser (EDFL) with a long cavity of figure-of-eight configuration. The EDFL generates a stable multiwavelength laser with 0.47 nm spacing at 24 mW threshold pump power, while the number of lines obtained increases with the pump power. A dark pulse emission is observed as the pump power is increased above 137 mW, with fundamental repetition rate of 29 kHz and pulse width of 2.7 µs. It is observed that the dark pulse train can be shifted to second-, third-, and fourth-order harmonic dark pulses by carefully adjusting the polarization controller. For the fundamental dark pulse, the maximum pulse energy of 32.4 nJ is obtained at pump power of 146.0 mW.